Towards a radical praxis in the struggle for democracy: contemporary challenges for the political and critical education on 21st Century (Práxis Educativa, 2020)
This paper advocates for the need of a radical political praxis in defense of democracy in the face of current contemporary challenges. Concepts based on the Critical Theory are discussed and updated, addressing central issues to democracy, social rights, culture and public policies in the 21st Century. When defending the argument that capitalism is not synonymous with democracy, the tension between economic neoliberalism and political authoritarianism is analyzed. It seeks to demonstrate how social and economic inequality in the case of Latin America results in the intensification of class conflict. It problematizes the way education ends up, by neoliberal logic, to the function of training for work to the detriment of its social, political, ethical, sensitive and human quality. It analyzes how the educational practice constitutes the object of political dispute between the neoliberal control tecniques and the progressive forces that defend a radical political education. Finally, it addresses the individual ethics, social morals, socio-historical consciousness and collective action necessary for a critical radical praxis, recovering the importance of hope in the process of social transformation.Keywords: Critical theory. Education. Praxis. Political formation. Democracy.